Protective Role of GPER Agonist G‐1 on Cardiotoxicity Induced by Doxorubicin. Issue 7 (16th February 2017) - De Francesco, Ernestina M.; Rocca, Carmine; Scavello, Francesco; Amelio, Daniela; Pasqua, Teresa; Rigiracciolo, Damiano C.; Scarpelli, Andrea; Avino, Silvia; Cirillo, Francesca; Amodio, Nicola; Cerra, Maria C.; Maggiolini, Marcello; et al.
Abstract : The use of Doxorubicin (Dox), a frontline drug for many cancers, is often complicated by dose‐limiting cardiotoxicity in approximately 20% of patients. The G‐protein estrogen receptor GPER/GPR30 mediates estrogen action as the cardioprotection under certain stressful conditions. For instance, GPER activation by the selective agonist G‐1 reduced myocardial inflammation, improved immunosuppression, triggered pro‐survival signaling cascades, improved myocardial mechanical performance, and reduced infarct size after ischemia/reperfusion (I/R) injury. Hence, we evaluated whether ligand‐activated GPER may exert cardioprotection in male rats chronically treated with Dox. 1 week of G‐1 (50 μg/kg/day) intraperitoneal administration mitigated Dox (3 mg/kg/day) adverse effects, as revealed by reduced TNF‐α, IL‐1β, LDH, and ROS levels. Western blotting analysis of cardiac homogenates indicated that G‐1 prevents the increase in p‐c‐jun, BAX, CTGF, iNOS, and COX2 expression induced by Dox. Moreover, the activation of GPER rescued the inhibitory action elicited by Dox on the expression of BCL2, pERK, and pAKT. TUNEL assay indicated that GPER activation may also attenuate the cardiomyocyte apoptosis upon Dox exposure. Using ex vivo Langendorff perfused heart technique, we also found an increased systolic recovery and a reduction of both infarct size and LDH levels in rats treated with G‐1 in combination with Dox respect to animals treated with Dox alone. Accordingly, the beneficial effects induced by G‐1 were abrogated in the presence of the GPER selective antagonist G15. These data suggest that GPER activation mitigates Dox‐induced cardiotoxicity, thus proposing GPER as a novel pharmacological target to limit the detrimental cardiac effects of Dox treatment. J. Cell. Physiol. 232: 1640–1649, 2017. © 2016 Wiley Periodicals, Inc. Abstract : 1. The potential beneficial effects of GPER activation in Doxorubicin (Dox)‐induced cardiotoxicity was evaluated. 2. In male rat heart, the treatment with the selective GPER ligand G‐1 prevented the increase in TNF‐α, IL‐1β, and LDH plasma levels induced by Dox. In Langendorff perfused rat heart, G‐1 also increased the systolic recovery at the end of ischemia and reduced infarct size and LDH levels triggered by Dox. Moreover, G‐1 attenuated the Dox‐induced myocyte apoptosis, as well as the inhibition of pro‐survival signaling cascades like ERK1/2 and AKT. Next, G‐1 counteracted the down‐regulation of BCL2 as well as the up‐regulation of apoptotic, inflammatory and fibrotic targets, such as BAX, iNOS, COX2, and CTGF induced by Dox. 3. Our study paves the way for further analyzing the role of GPER as pharmacological target in novel therapeutic strategies aimed to prevent the cardiotoxicity exerted by Dox.